2009
DOI: 10.1007/s10926-009-9211-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Role of Occupational Health and Safety Interventions in the Prevention of Upper Extremity Musculoskeletal Symptoms, Signs, Disorders, Injuries, Claims and Lost Time

Abstract: It is difficult to make strong evidenced-based recommendations about what practitioners should do to prevent or manage upper extremity MSDs. There is a paucity of high quality OHS interventions evaluating upper extremity MSDs and none focused on traumatic injury outcomes or workplace mandated pre-placement screening exams. We recommend that worksites not engage in OHS activities that include only workstation adjustments. However, when combined with ergonomics training, there is limited evidence that workstatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
133
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 116 publications
2
133
0
1
Order By: Relevance
“…Participant 1's chair was similar to the intervention chairs, but lacked full adjustability. The effect of arm rests on pain and symptoms has been shown in the review by Kennedy et al (2010) to have a positive influence on upper quadrant pain and symptoms. However, not all studies on the subject concur as some studies show no effect (Brewer et al 2006).…”
Section: Limitations and Recommendationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Participant 1's chair was similar to the intervention chairs, but lacked full adjustability. The effect of arm rests on pain and symptoms has been shown in the review by Kennedy et al (2010) to have a positive influence on upper quadrant pain and symptoms. However, not all studies on the subject concur as some studies show no effect (Brewer et al 2006).…”
Section: Limitations and Recommendationsmentioning
confidence: 96%
“…Studies into the effectiveness of ergonomic interventions for musculoskeletal symptoms evaluate combined interventions and rarely research the benefit of the chair alone (Brewer et al 2006, Kennedy et al 2010. A review by van Niekerk et al (2012) showed a trend supporting the use of ergonomic office chairs to reduce upper quadrant muscle activity as well as a reduction in the intensity of the symptoms, although the chair was not the sole intervention in some of the studies reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent study by Van Eerd and coworkers [20], if no significant actions are undertaken by occupational health and safety practitioners, MSDs may become the leading cause of long absences from work and, even worse, cause permanent disabling effects. According to recent literature ( [21,22], several workplace interventions have been implemented so far. Unfortunately, only a few studies have demonstrated that such measures had sustainable and quantifiable positive effects on symptoms and disability outcomes, although none have shown negative effects.…”
Section: Highlight By Alessandro Castorinamentioning
confidence: 99%
“…Moreover, work modification is effective in helping subjects with MSD return to work (15). Another recent review (16), focusing only on upper-extremity disorders, concluded that due to the low number of high-quality studies, it is difficult to make strong evidenced-based recommendations. However, the authors discouraged activities that would engage only workstation adjustments.…”
mentioning
confidence: 99%
“…However, the authors discouraged activities that would engage only workstation adjustments. Some positive but limited evidence was found for ergonomics training combined with workstation adjustments (16).…”
mentioning
confidence: 99%